ANALISIS PEMECAHAN MASALAH KONSEP USAHA PADA MAHASISWA CALON GURU FISIKA - Alfani, Alfani; Supriyatman, Supriyatman (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This study aims to describe the problem-solving ability of business concepts in prospective students of physics teachers. Based on Heller's stages in terms of high, medium, and low categories. This type of research is qualitative. The subjects of this study were students of the class of 2020, 6 respondents were selected consisting of 2 high categories, 2 medium categories, and 2 low categories. The results of this study are: 1) the stage of visualizing student problems in the high and medium categories is quite good while for the low category it is still lacking. 2) In the stage of describing physics concepts based on problems, students in the high and medium categories are good at writing things that are known and asked, while for the low category they are still lacking because they only write part of the information they know. 3) planning solutions for the high and medium categories are good, while for the low categories it is still lacking because of planning solutions to existing problems. 4) the stage of implementing the solution plan for the high and medium categories is very good at implementing the existing solutions while for the low category it is still lacking because they do not understand the existing problems. 5) the stages of checking and evaluating solutions for the high and medium categories have re-checked the steps to solve the problem while for the low category they did not check because they could not solve the given problem.